Characteristics of Particleboard from Sorghum and Nypa Fruit Skin Fiber Bonded with Citric Acid-Sucrose Adhesive - Romauli Tampubolon; Evi Sribudiani; Sonia Somadona; Yusup Amin; Sukma Surya Kusumah (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Sorghum (Sorghum bicolor L.) and nypa fruit skin fiber (Nypa fruticans Wurmb.) can be used as raw materials in the manufacture of eco-friendly particleboard (PB) using natural adhesives based on citric acid and sucrose. This study aimed to determine the characteristics of PB from sorghum and nypa fruit skin fiber using citric acid-sucrose adhesive and also to determine the optimum composition of raw materials and adhesives in the manufacture of PB. The PB panel was made by mixing raw materials and adhesives with variations in the composition of nypa fruit skin fiber:sorghum raw materials 100:0, 25:75, 50:50, and 0:100, and variations in the concentration of citrate-sucrose adhesive were 20% and 30%. The target dimensions and density of PB were 25 cm x 25 cm x 0.9 cm and 0.8 g/cm3, respectively. The PB was hot-pressed for 10 min at 200oC with a pressure of 11 MPa. The physical and mechanical properties of PB were determined using the Japanese Industrial Standard (JIS) A 5908:2003 standard. The results showed that the PB has average values of moisture content of 11.94%, density of 0.79 g/cm3, water absorption of 52.96%, thickness swelling of 13.21%, modulus of elasticity of 1029.55 N/mm2, modulus of rupture of 6.46 N/mm2, internal bonding of 0.18 N/mm2, and screw holding power of 43.12 N. Variation of raw materials composition has a significant effect moisture content, water absorption, thickness swelling, modulus of elasticity, and modulus of rupture. Applying 30% adhesive content significantly affected water absorption, thickness swelling, and screw holding power. Keywords: citric acid-sucrose, nypa fruit skin, particleboard, sorghum